Christian-Muslim Relations. A Bibliographical History Volume 16 North America, South-East Asia, China, Japan, and Australasia (1800-1914) - Chesworth, John A.; Thomas, David (The History of Christian-Muslim Relations, 2020)
Christian-Muslim Relations. A Bibliographical History 16 (CMR 16) covering North America, South-East Asia, China, Japan and Australasia in the period 1800-1914, is a further volume in a general history of relations between the two faiths from the 7th century to the early 20th century. It comprises a series of introductory essays and the main body of detailed entries. These treat all the works, surviving or lost, that have been recorded. They provide biographical details of the authors, descriptions and assessments of the works themselves, and complete accounts of manuscripts, editions, translations and studies. The result of collaboration between numerous leading scholars, CMR 16, along with the other volumes in this series, is intended as a basic tool for research in Christian-Muslim relations. Section Editors: Clinton Bennett, Luis F. Bernabe Pons, Jaco Beyers, Emanuele Colombo, Lejla Demiri, Martha Frederiks, David D. Grafton, Stanisław Grodź, Alan Guenther, Vincenzo Lavenia, Arely Medina, Alain Messaoudi, Gordon Nickel, Claire Norton, Reza Pourjavady, Douglas Pratt, Radu Păun, Charles Ramsey, Peter Riddell, Umar Ryad, Mehdi Sajid, Cornelia Soldat, Karel Steenbrink, Charles Tieszen, Carsten Walbiner, Catherina Wenzel.